THE LEGAL PROTECTION AND DISPUTE RESOLUTION IN PEER TO PEER LENDING-BASED FINANCIAL TECHNOLOGY ASPECT - Denny Suwondo (Jurnal Pembaharuan Hukum, 2023)
The purpose of this research is to find out the legal protection for peer to peer lending consumers in Indonesia and analyze dispute resolution in peer to peer lending. This research was conducted using normative legal research methods. The author uses normative juridical research methods because the research is carried out on the norms that are materialized in the relevant laws and regulations. The results of this study are Legal protection for consumers of peer to peer lending-based financial technology consists of criminal legal protection, civil legal protection, and preventive legal protection with the establishment of rules or regulations that prevent the use of Fintech peer to peer Lending services as a means of economic crime. Fintech dispute resolution can be done by litigation and non-litigation.